Spatial pattern and influential factors for early marriage: evidence from Bangladesh Demographic Health Survey 2017-18 data - Md Arif Billah; Md. Mostaured Ali Khan; Syed Manzoor Ahmed Hanifi; M. Mofizul Islam; Md. Nuruzzaman Khan (BMC, 2023)
Abstract Background Early marriage is highly prevalent in Bangladesh. It is linked with a range of adverse outcomes, including maternal and child mortality. However, research on regional variations and factors associated with early marriage is scarce in Bangladesh. This study aimed to explore the geographical variations and predictors of early marriage in Bangladesh. Methods Data of women aged 20-24 in the Bangladesh Demographic and Health Survey 2017-18 were analysed. The occurrence of early marriage was the outcome variable. Explanatory variables were several individual-, household- and community-level factors. Geographical hot spots and cold spots of early marriage were first determined using Global Moran's I statistic. Multilevel mixed-effect Poisson regression was used to determine the association of early marriage with individual-, household-, and community-level factors. Results Almost 59% of women aged 20-24 reported they were married before reached 18. The hotspots of early marriage were mainly concentrated in Rajshahi, Rangpur and Barishal, and the cold spots were in Sylhet and Chattogram divisions. The prevalence of early marriage was lower among higher educated (adjusted prevalence ratio (aPR): 0.45; 95% CI: 0.40, 0.52), and non-Muslim women (aPR: 0.89; 95% CI: 0.79, 0.99) than their counterparts. Higher community-level poverty was significantly associated with early marriage (aPR, 1.16; 95% CI: 1.04, 1.29). Conclusion The study concludes that promoting girls' education, awareness-building programs about the adverse effects of early marriage and proper application of the child marriage restraint act, particularly in disadvantaged communities are recommended.